Physiological and biochemical responses to cold and drought in the rock-dwelling pulmonate snail, Chondrina avenacea. - Rozsypal, Jan (Jihočeská univerzita, 2013)
We assessed the capacity of rock-dwelling snail, Chondrina avenacea to tolerate environmental stress during seasonal alterations of activity and dormancy. We examined whether hibernation and aestivation share some physiological and biochemical traits, which can underlie potential development of cross-tolerance (i.e., high cold tolerance during estivation or high drought tolerance during hibernation). For this purpose, we recorded seasonal changes in the levels of cold, drought and anoxia tolerance and changes in basic physiological and biochemical parameters which are linked to dormancy and stress tolerance such as supercooling capacity, mass and hydration, rate of exchange of respiratory gases, total amount of proteins, lipids and glycogen, and metabolomic composition.
Physiological and biochemical responses to cold and drought in the rock-dwelling pulmonate snail, Chondrina avenacea.